Kapan Allah Membuat Segalanya Indah: Misteri Waktu dalam Kitab Pengkhotbah 3:11 - Nursantosa, Andre Putranto (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
“God makes each thing beautiful in its time.” This quote has somewhat found its common usage in social media. People have some habit of quoting this expression whenever they encounter difficulties so as to comfort themselves. Through these words, a person might hope earnestly that “God will help me or provide me with the ‘beautiful’ time someday.” But the question that immediately follows is “When?” What if the burden stays and life remains unchanged? Not many of the fans of these wise words know that the saying originates from the Book of Ecclesiastes (3:11), which in itself is a form of ancient Hebrew literature. In the complete verse of the Book, the clause “He hath made every thing beautiful in his time is followed by another clause, “also he hath set the world in their heart, so that no man can find out the work that God maketh from the beginning to the end.” The later part of the verse (3:11b) is often ignored. However, by accepting the words that “God hath set the world in their heart”, one realises that he or she cannot fathom God’s mind, but might make peace and accept that divine question. Hence, one might realise that both good times and the not-so-good times could be but “beautiful times” for oneself.